Pengaruh Etos Kerja, Budaya Organisasi Dan Beban Kerja Terhada Kinerja Karyawan Di Tengah Pandemi Covid 19 (Studi Ayam Bakar Wong Solo Malang) - Moh. Naufal Syahriza; Pardiman Pardiman; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims to determine and analyze the effect of work ethic, organizational culture, and workload on employee performance on chicken roasted wong solo in Malang. This research is a type of explanatory research, with a quantitative approach. The analytical method used is multiple linear regression analysis. The sample used in this study used a saturated sample of only 57 employees.The results of this study indicate that partially there is a significant influence between work ethic on employee performance, organizational culture has a significant effect on employee performance, workload has a significant effect on employee performance at chicken grilled wong solo in the city of Malang. And the results of this study indicate that simultaneously there is a significant influence between work ethic, organizational culture and workload on employee performance at chicken roasted wong solo in the city of Malang. Keywords: of work ethic, organizational culture, workload and employee performance